EKONOMI POLITIK PERDAGANGAN GULA DiI INDONESIA Political Economy of Sugar Trade in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
The sugar trade is a sub system of the sugar system. The state has been controled wholly for both of the sugar industries system and the sugar trade system. It relates on the interest of the state to stabilize condition of the main food. Interest of the state manivested on many goverment decisions. Especially for the sugar trade system (this study focuses), there are extremely control. To the private sugar trader, goverment collects them on the formal association. From this organization (Gapegti) sugar allocating for distribution will be given out by. The private sugar trader which has never been registered in this association can not do trading. So the registered sugar trader is labeled a lucky group but they must be called by the middle class depend on the state. The analysis of this study is instabilization of the sugar trading (point to the historical back ground held on 1951, 1968, 1969, 1969, 1975) leads the goverment to control the trade systeni closely. So, because that the distribution of power between state and the mass is unbalance. The centralization of the middle class is not a good situation for the democracy. This study supports the statement that democracy in Indonesia does not come yet because the state is strongest and there is no middle class is able to challenge its power.